COMPUTATIONAL STUDY OF ORGANIC COMPOUNDS – AN APPLICATION FOR LEARNING IN CHEMISTRY (Revista Ifes Ciência, 2019)
Organic chemistry is a theme not so easy to understand by undergraduating students. The motivation of this work was carried out computational study of three different molecules by molecular modeling using classic and semi-empirical methods besides open-source softwares. The optimized structures were visualized through 3D representations which made the study more understanding. Physical chemistry properties were extracted from all molecules. For the molecule one there was good correlation between the calculation methods. For the molecule two and more complex structures like molecule three and four there was possible influence of steric effect showing that each method is applicable for each study system.